In vitro Comparative Study for Anti-proliferative Activity of Some Plant Extracts, Fam. Apiaceae, on HeLa Cell Line - Sara E. Gomaa; Matthew Friedersdorf; Hesham Ali El Enshasy; MB Abou-Donia (Faculty of Pharmacy Universitas Gadjah Mada, Yogyakarta, Skip Utara, 55281, Indonesia, 2020)
In this research, the biological activities of five plant extracts from family Apiaceae; Italian Parsley (Petroselinum neapolitanum), Fennel (Foeniculum vulgare), Celery (Apium graveolens), Cilantro (Coriandrum sativum) and Dill (Anethum graveolens), were studied. Antiproliferative effect of eleven ethanol crude extracts was tested in Human Cervical (Hela) cancer cells. Results clearly demonstrated that all plant extracts showed high significant difference when compared to the negative control (DMSO).Parsley leaves extract, cilantro leaves extract and cilantro stems extract showed no significant difference with the positive control (Actinomycin D). As for, fennel bulb extracts, fennel stalks extracts, celery stems gave better results than the positive control with no significant difference through the 24, 48 and 72 h treatment. There were no significant difference between Fennel extracts and the positive control, which showed high effect on the cancer cells survival. There were no significant difference between both extracts of Cilantro leaves and stems through each time but the best result was after 72 h of treatments. Regarding Dill leaves and stems, cell numbers recorded no significant difference between the both on time dependent manner. Further investigation for ethanolic extracts of parsley leaves, fennel bulb, fennel stalks, celery stems, cilantro leaves and cilantro stems which showed better results than using the commercial drug Actinomycin D (25ml/ml) for 24 h treatment or less depending on concentrations manner. Also, further investigation on different types of cancer cell lines to avoid the toxic effect of chemotherapy.